2007
DOI: 10.1128/mcb.00866-07
|View full text |Cite
|
Sign up to set email alerts
|

An EGR2/CITED1 Transcription Factor Complex and the 14-3-3σ Tumor Suppressor Are Involved in Regulating ErbB2 Expression in a Transgenic-Mouse Model of Human Breast Cancer

Abstract: Amplification and elevated expression of the ErbB2 receptor tyrosine kinase occurs in 20% of human breast cancers and is associated with a poor prognosis. We have previously demonstrated that mammary tissuespecific expression of activated ErbB2 under the control of its endogenous promoter results in mammary tumor formation. Tumor development was associated with amplification and overexpression of ErbB2 at both the transcript and protein levels. Here we demonstrate that the EGR2/Krox20 transcription factor and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 49 publications
2
33
0
Order By: Relevance
“…One likely explanation for these observations is that 14-3-3σ negatively regulates transcription factors involved in regulating ErbB2 expression. Consistent with this concept, one previous study has demonstrated that 14-3-3σ is involved in sequestration of the EGR2 transcription factor that directly activates the erbB2 promoter (16). Given that the expression of the activated erbB2 allele is driven by the endogenous erbB2 promoter in the ErbB2 KI model, there is strong selective pressure for the loss of 14-3-3σ expression.…”
Section: Discussion Loss Of 14-3-3s Is a Critical Event In Erbb2 Mammsupporting
confidence: 50%
See 4 more Smart Citations
“…One likely explanation for these observations is that 14-3-3σ negatively regulates transcription factors involved in regulating ErbB2 expression. Consistent with this concept, one previous study has demonstrated that 14-3-3σ is involved in sequestration of the EGR2 transcription factor that directly activates the erbB2 promoter (16). Given that the expression of the activated erbB2 allele is driven by the endogenous erbB2 promoter in the ErbB2 KI model, there is strong selective pressure for the loss of 14-3-3σ expression.…”
Section: Discussion Loss Of 14-3-3s Is a Critical Event In Erbb2 Mammsupporting
confidence: 50%
“…It has also been demonstrated that all human ErbB2-overexpressing breast cancer cell lines have no or reduced 14-3-3σ expression (25). Further molecular analyses suggested that selection for loss of 14-3-3σ may in part be related to its ability to sequester the EGR2/ CITED1 transcription factor complex in the cytoplasm and thus interfere with its capacity to transactivate the endogenous erbB2 promoter (16). Taken together, these data argue that, in addition to sequestration of key translation and cellcycle components, 14-3-3σ can directly modulate the transcription of ErbB2 through relocalization of key transcription factors involved in its transcriptional activation.…”
Section: Loss Of 14-3-3s Results In Both Accelerated Erbb2 Mammary Tumentioning
confidence: 99%
See 3 more Smart Citations